Alterations in peripheral blood B cell subsets and dynamics of B cell responses during human schistosomiasis. - Lucja A Labuda; Ulysse Ateba-Ngoa; Eliane Ngoune Feugap; Jorn J Heeringa; Luciën E P M van der Vlugt; Regina B A Pires; Ludovic Mewono; Peter G Kremsner; Menno C van Zelm; Ayola A Adegnika; Maria Yazdanbakhsh; Hermelijn H Smits (Public Library of Science (PLoS), 2013)
Antibody responses are thought to play an important role in control of Schistosoma infections, yet little is known about the phenotype and function of B cells in human schistosomiasis. We set out to characterize B cell subsets and B cell responses to B cell receptor and Toll-like receptor 9 stimulation in Gabonese schoolchildren with Schistosoma haematobium infection. Frequencies of memory B cell (MBC) subsets were increased, whereas naive B cell frequencies were reduced in the schistosome-infected group. At the functional level, isolated B cells from schistosome-infected children showed higher expression of the activation marker CD23 upon stimulation, but lower proliferation and TNF-α production. Importantly, 6-months after 3 rounds of praziquantel treatment, frequencies of naive B cells were increased, MBC frequencies were decreased and with the exception of TNF-α production, B cell responsiveness was restored to what was seen in uninfected children. These data show that S. haematobium infection leads to significant changes in the B cell compartment, both at the phenotypic and functional level.